The Application of the Team-Games Tournament Model Assisted by Wordwall Media to the Learning Outcomes of Pancasila Education Grade IV SD Negeri 22 Lubuklinggau - Maharani, Fitria; Frima, Aren; Abadi, Candres (Civiliza Publishing, Indonesia., 2025)
The use of learning models plays a crucial role in realizing the learning targets that have been set. This study aims to determine the completeness of the learning outcomes of Pancasila education of grade IV students at SD Negeri 22 Lubuklinggau after the implementation of the Teams Games Tournament model with the help of Wordwall media. The research method used is quantitative with experimental methods. This study uses a pre-experimental design with one group pre-test and post-test categories. The results of the study showed that based on the results of the analysis of the final student data hypothesis test calculation, a tcal value (4.31) was obtained. Based on the results of the post-test value test with a significant level of α = 0.05, the table (1.720) was obtained. Thus it is obtained that tcount (4.31) ≥ ttable (1.720) by this means that Ha is accepted and Ho is rejected. So, it can be concluded that the Teams Games Tournament learning model assisted by Wordwall media can complete the learning outcomes of Pancasila Education for grade IV students of SD Negeri 22 Lubuklinggau.